A pilot study exploring the effects of musical genres on the depth of general anaesthesia assessed by haemodynamic responses. Issue 8 (August 2016) - Mira, Filipa; Costa, Alexandra; Mendes, Eva; Azevedo, Pedro; Carreira, L Miguel
Objectives: This pilot study aimed to investigate whether and how music and musical genres may influence the depth of anaesthesia, as measured using changes in arterial blood pressure (ABP), including systolic blood pressure (SBP), and heart rate (HR) across three different surgical time points. Methods: This work focused on a sample of 12 female cats ( Felis catus ) that were subjected to an elective ovariohysterectomy (OVH), and three different surgical time points were considered (T1, coeliotomy; T2, ligature placement and transection of the ovarian pedicle; and T3, ligature placement and transection of the uterine body). All of the cats were subjected to stimulation with 2 min segments of three music tracks from different genres (pop [PM], classical [CM] and heavy metal [HM]). At the same time, ABP and HR measurements were obtained using a multi-parametric monitor. For statistical analysis, P values <0.05 were considered significant. Results: For all cats, music exposure induced statistically significant changes in the parameters under study; the same finding was observed for the genre of music. The majority of cats experienced the same variation pattern, with lower values when exposed to CM, intermediate values when exposed to PM and higher values when exposed to HM. Conclusions and relevance: Our results indicate that the development of sensory processing of acoustic stimuli is maintained by cats under general anaesthesia and reveal the influence of music on the autonomous nervous system, as measured using HR and SBP.